Penerapan Internet Of Things Pada Aplikasi Alat Deteksi Dan Monitoring Tekanan Darah - Winarno Fadjar Bastari; Akbar Sujiwa; Rizky Setyobudi (LPPM Universitas PGRI Adi Buana, 2023)
In the medical world known as a tool to measure the value of blood pressure called a sphygmomanometer. There are 2 types of Tensimeter tools that are often used, namely the analog type which is the old version and the digital type which is the new version. Then it is known that the development of Android smartphones in the present is increasingly sophisticated, with the addition of various features. From the Android Tensimeter and Smartphone device, the authors plan to create a digital Tensimeter device that can detect blood pressure values and record all measurement results that have been carried out, so that at any time the patient can always monitor the value of his own blood pressure via an Android Smartphone. In this case the digital blood pressure detection tool is integrated with IOT (internet of things), so that it becomes a blood pressure detection and monitoring tool. To process data and connect to the internet, the NodeMCU ESP8266 controller is used. While the MPX5050GP sensor is used as a means of detecting blood pressure values. Then the sensor will send all blood pressure calculation data to Firebase which functions as the data storage center. In the next stage via a smartphone, all data will be accessible and monitored. Next, it can be informed that from the test results on the sphygmomanometer that was made and tests on the sphygmomanometer used as a comparison, there is a difference in accuracy of about 1 percent